MARK 2 : 18-22: AN EXERCISE IN THEORETICALLY-FOUNDED EXEGESIS - Maartens, P. J. (Scriptura, 1980)
The aim of this article is to propose a methodological approach to a theoretically-founded exegesis of Mark 2 : 18-22. Theoretically-founded exegesis is an explication of the language and structure of a given text against its socio-cultural and historical background in order to give the reader a better understanding of the text.